Norma Sosial dan Kepatuhan Pajak - Endah Wening Budiningrum (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2024)
The purpose of this study is to explore the role of social norms in tax compliance in Indonesia. This study draws on Cialdini & Trost, (1998), taxonomy of social norms to descriptive norms, injunctive norm, subjective norm and personal norm. Hypotheses this study is regarding the direct and indirect influences of social norms. This study use 128 participants, the participants are college students who took courses in taxation dan SMEs management and they had business activities. The hypotheses testing in this study used SEM (Structural Equation Modeling). The SEM analysis tool used SEM PLA (Partial Least Squares) WarpPLS 7.0. Result of the path analysis show that descriptive norm, injunctive norm, subjective norm each have a direct influence on tax compliance. Descriptive norms are indirectly influence to tax compliance through injunctive norm and subjective norm. Subjective norm direct influence but not indirect influence on tax compliance. personal norm are not directly influence to tax compliance